Upaya Meningkatkan Motivasi Belajar PAI Kelas 4 SDN Bumirejo Melalui Model Pembelajaran Discovery Learning - Muti’ah, Mei Dwi; Multazamah, Ulfatun (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to determine the increase in learning motivation in the fourth grade of SD N 4 Bumirejo. The model used is a classroom action research model with one cycle. Cycle I was carried out in one meeting with four stages of activities, namely, planning, action, observation, and reflection. The subjects of the study were 16 fourth grade students of SD N 4 Bumirejo. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used interactive analysis with stages, namely data condensation, data presentation, and conclusion drawing. The results of the pre-cycle study showed that the average result of student learning motivation was 46.25%, and increased in cycle I with a percentage of 68.75% after implementing the discovery learning model. Therefore, it can be concluded that learning with the discovery learning model can increase student learning motivation.